Evaluating the efficacy of the new electronic dental assistant training program - Xitian Tang; Wenzhen Gu; Yao Hu; Minghui Yan (Scientific Reports)
Abstract With the rapid development of global medical informatization, information systems have become a critical part of the nursing profession The training of dental assistants lacks specialized information management tools, resulting in increasing difficulty in time-consuming training management. To evaluate a new electronic dental assistants self-design training program and examine its effects on informatization management. A self-design training management system was developed. The core module of the system, the clinical training management module, consisted of six different parts: resource management, course management, examination assessment, student management, teacher management, and evaluation management. 137 dental assistants were enrolled to complete the training and assessed through the system. With the introduction of the new system, the coverage of the required courses arranged by the nursing department increased from 80.29 to 100% (P < 0.01). The average time for the training supervisors to complete the evaluation of dental assistants’ monthly examination significantly decreased from (94.80 ± 28.95) to (8.30 ± 3.30) minutes (P < 0.05). The pass rate of the N2-level promotion test increased from 68.18 to 100% (P < 0.01). The four-hand operation response time of outpatient dental assistants was significantly decreased from (5.42 ± 0.83) to (3.37 ± 0.76) seconds (P < 0.05); The satisfaction score of 94.2% of doctors on dental assistants passed 44 points, 95.6% of dental assistants and 100% training supervisors rated the training management system on satisfaction score of more than 36 points. This training management system significantly enhances the training experience for dental assistants, not only by boosting participation rates but also by streamlining training management time and elevating the overall quality of training along with staff satisfaction. This study highlights the potential for electronic management systems to enhance the quality and efficiency of dental assistant training globally.